Intense Investing as Part of the Modern Activities of an Industrial Enterprise - Riabykina Nataliia I.; Riabykina Kateryna H. (Bìznes Inform, 2023)
The aim of the article is to study the issues of the need to implement the economic interests of enterprise by carrying out investment activity, taking into account its features. The article states that the implementation of the sequence of activities – from the selection of effective investment objects, the formation of an investment program, the attraction of investment resources up to the accomplishment of plans – is a matter that succeeds only in enterprises that are trusted, which openly and transparently carry out their activities, maintain a good reputation, have both the well-developed in the past and the long-term plan of activities, have convinced investors of a real opportunity to make a profit on their deposits in the near future. That is, enterprises need that a favorable investment climate be ensured. It is determined that this task remains unfulfilled due to the low investment activity of enterprises. As a result of the rather difficult political situation and the imposition of martial law in the country, the investment activity of enterprises does not ensure the proper effectiveness and efficiency of production. The article notes that the issues related to the study of investment activity of enterprises are considered by many scholars. All of them understand that in the modern economy the level of investment activity is one of the most accurate signs that characterize the quality of economic growth, the possibility of social progress, is formed under the influence of political, economic, legal, social and other factors that determine investment opportunities and investment risks. Analysis of approaches to determining the investment activity of enterprise makes it possible to conclude that intense investing is a complex characteristic of investment activity, reflects the level of intensity of investment in production and economic activity in order to achieve sustainable development of enterprise. It is substantiated that the solution of the issue of increasing the level of investment activity is quite relevant, and first of all – for enterprises in the sphere of material production. An analysis of the investment activity of JSC «Kryvyi Rih Iron Ore Plant» has been carried out. The results of this analysis can be used as a preparatory stage for determining the indicators of investment activity, the volume and pace of attracting investments in order to increase the level of efficiency of the main activity of enterprise.